The Effect of Dietary Counseling on Nutrient Intakes in Gastric Banding Surgery Patients. (1st December 2013) - Shah, Meena; Adams-Huet, Beverley; Rao, Sneha; Snell, Peter; Quittner, Claudia; Garg, Abhimanyu
Abstract : Background: There is some evidence that bariatric surgery patients who undergo the purely restrictive procedures, such as the gastric banding (GB) or the vertical banded gastroplasty surgery, do not meet the dietary reference intakes for several nutrients. Whether dietary counseling improves micronutrient and macronutrient intakes was examined in GB surgery patients. Methods: Twenty-three GB surgery patients received dietary and behavioral counseling for 12 weeks to limit energy intake and improve nutrient intakes. Food intake was assessed by 3-day food record at baseline and 6 and 12 weeks. Postintervention data were available in 21 patients. Results: At baseline, more than 50% of the subjects reported inadequate dietary intakes of 13 nutrients but overconsumption of sodium and percent energy from saturated and trans–fatty acids. Mixed-effects model for repeated measures revealed a significant reduction in energy ( P = 0.0007), absolute protein ( P = 0.04), cholesterol ( P = 0.045), and potassium ( P = 0.01) intake and an increase in vitamin K ( P = 0.03) intake and percent energy from protein ( P = 0.005) during the 12 weeks. The McNemar test showed a reduction in the proportion of the subjects with an inadequate intake of vitamin K ( P = 0.008) but an increase in the proportion of the subjects with an inadequate intake of thiamin ( P = 0.03) at 12 weeks. The proportion of the subjects who did not meet the nutrient requirements for the remaining 27 nutrients was generally high and remained unchanged. Conclusions: Dietary intervention improved the intake of some nutrients in the GB surgery patients. However, most nutrient intake requirements remained unmet by many subjects. These results indicate that nutritional counseling beyond 12 weeks is warranted in GB surgery patients to improve their dietary nutrient intakes.